2014
DOI: 10.1364/ol.39.006899
|View full text |Cite
|
Sign up to set email alerts
|

Split-mode fiber Bragg grating sensor for high-resolution static strain measurements

Abstract: We demonstrate a strain sensor with very high sensitivity in the static and low frequency regime based on a fiber ring cavity that includes a π phase-shifted fiber Bragg grating. The grating acts as a partial reflector that couples the two counter-propagating cavity modes, generating a splitting of the resonant frequencies. The presence of a sharp transition within the π phase-shifted fiber Bragg grating's spectral transmittance makes this frequency splitting extremely sensitive to length, temperature, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 13 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…In References [ 26 , 27 , 28 , 29 , 30 ], FBG gratings are inserted into ring resonators made of optical fibre connected one end to other to create resonant FBGs strain sensors. These resonant sensor systems are mainly built using FBGs with complex scattering sources (SCs) which couple two counter-propagating modes (traveling wave (TW)) in a ring resonator.…”
Section: Operation Principle Of Splitting Mode Strain Sensors Basementioning
confidence: 99%
See 1 more Smart Citation
“…In References [ 26 , 27 , 28 , 29 , 30 ], FBG gratings are inserted into ring resonators made of optical fibre connected one end to other to create resonant FBGs strain sensors. These resonant sensor systems are mainly built using FBGs with complex scattering sources (SCs) which couple two counter-propagating modes (traveling wave (TW)) in a ring resonator.…”
Section: Operation Principle Of Splitting Mode Strain Sensors Basementioning
confidence: 99%
“…The mode-splitting spectral feature of FBGRRs allows one to measure the strain with a far greater accuracy, making these sensors particularly suited for the structural health-monitoring in civil infrastructures, aerospace, energy, and maritime operations fields. The main advantages of FBGRRs, with respect to the conventional FBG sensors, are represented by a cavity enhanced resolution, which leads to an improved sensing resolution [ 30 ], insensitivity to environmental perturbations [ 26 ] and lower production costs because, differently from conventional FBG sensors, the sensing scheme is self-referenced and there is no need of a reference signal to perform accurate measurements [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Operation Principle Of Splitting Mode Strain Sensors Basementioning
confidence: 99%
“…Several configurations of MRR spectroscopic sensors utilising the split mode feature arising from the presence of an intracavity scattering element or surface roughness are studied that aim to provide a new generation of optical technologies which perform better in terms of optical sensing [7,8,11]. The mode-splitting technique has enabled the possibility of high sensitivity particle detection [11,12], strain measurement [13], optical bend sensing [14], defect sensing in carbon nanotubes [15] etc... Recently, it has been demonstrated that MRR systems that includes distributed Bragg reflectors (DBRs) also exhibit split modes in their spectral response also making them a candidate for spectral sensors [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of replacing typical Bragg gratings with BGRR is reported in [21], while the guidelines for a band edge slow light magnification together with a Q-factor enhancement are given in [22]. In the frame of strain sensors, the fiber BGRRs (i.e., FBGRRs) have been proposed and experimentally investigated as splitting mode resonant sensors, due to their enhanced performance [23][24][25]. For this purpose, in this paper we investigate, for the first time to the best of our knowledge, the effect of the rotation Ω on FBGRRs and π-shifted FBGRRs (i.e., defective FBGRRs), whose schemes are sketched in Figs.…”
Section: Introductionmentioning
confidence: 99%